The potential for quality assurance systems to save costs and lives: the case of early infant diagnosis of HIV. Issue 10 (26th August 2020) - Terris‐Prestholt, F.; Boeras, D.; Ong, J. J.; Torres‐Rueda, S.; Cassim, N.; Mbengue, M. A. S.; Mboup, S.; Mwau, M.; Munemo, E.; Nyegenye, W.; Odhiambo, C. O.; Dabula, P.; et al.
Abstract: Objectives: Scaling up of point‐of‐care testing (POCT) for early infant diagnosis of HIV (EID) could reduce the large gap in infant testing. However, suboptimal POCT EID could have limited impact and potentially high avoidable costs. This study models the cost‐effectiveness of a quality assurance system to address testing performance and screening interruptions, due to, for example, supply stockouts, in Kenya, Senegal, South Africa, Uganda and Zimbabwe, with varying HIV epidemics and different health systems. Methods: We modelled a quality assurance system‐raised EID quality from suboptimal levels: that is, from misdiagnosis rates of 5%, 10% and 20% and EID testing interruptions in months, to uninterrupted optimal performance (98.5% sensitivity, 99.9% specificity). For each country, we estimated the 1‐year impact and cost‐effectiveness (US/DALY averted) of improved scenarios in averting missed HIV infections and unneeded HIV treatment costs for false‐positive diagnoses. Results: The modelled 1‐year costs of a national POCT quality assurance system range from US 69 359 in South Africa to US 334 341 in Zimbabwe. At the country level, quality assurance systems could potentially avert between 36 and 711 missed infections (i.e. false negatives) per year and unneeded treatment costs between US 5808 and US 739 030. Conclusions: The model estimates adding effective quality assurance systems are cost‐saving in four of the five countries within the first year. Starting EQA requires an initial investment but will provide a positive return on investment within five years by averting the costs of misdiagnoses and would be even more efficient if implemented across multiple applications of POCT. Abstract : Objectifs: L'intensification du dépistage au point des soins (DPS) pour le diagnostic précoce du VIH chez le nourrisson (DPVN) pourrait réduire le grand écart dans le dépistage des nourrissons. Cependant, un DPVN DPS sous‐optimal pourrait avoir un impact limité et des coûts évitables potentiellement élevés. Cette étude modélise la rentabilité d'un système d'assurance qualité pour traiter les performances des tests et les interruptions de dépistage, dues par exemple à des ruptures de stock, au Kenya, au Sénégal, en Afrique du Sud, en Ouganda et au Zimbabwe, avec des épidémies variables du VIH et des systèmes de santé différents. Méthodes: Nous avons modélisé une qualité de DPVN soulevée par le système d'assurance qualité à partir de niveaux sous‐optimaux: c'est‐à‐dire des taux d'erreurs de diagnostic de 5%, 10% et 20% et des interruptions des tests de DPVN en mois, à des performances optimales ininterrompues (sensibilité de 98, 5%, spécificité de 99, 9%). Pour chaque pays, nous avons estimé l'impact sur un an et la rentabilité (en USD/DALY évitée) de scénarios améliorés pour éviter les infections à VIH manquées et les coûts inutiles de traitement du VIH pour les diagnostics faux positifs. Résultats: Les coûts modélisés sur un an d'un système national d'assurance qualité DPS vont de 69.359 USD en Afrique du Sud à 334.341 USD au Zimbabwe. Au niveau des pays, les systèmes d'assurance de la qualité pourraient potentiellement éviter entre 36 et 711 infections manquées (c'est‐à‐dire des faux négatifs) par an et des coûts de traitement inutiles entre 5.808 et 739.030 USD. Conclusions: Le modèle estime que l'ajout de systèmes d'assurance qualité efficaces permet de réaliser des économies dans quatre des cinq pays au cours de la première année. Le lancement de l'assurance qualité nécessite un investissement initial, mais fournira un retour sur investissement positif dans les cinq ans en évitant les coûts des diagnostics erronés et serait encore plus efficace s'il était mis en œuvre dans plusieurs applications de DPS.